Hidden germ of the immunocompromised: a case of fungal orbital cellulitis - Er, Lay Ze; Johar MJ, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Orbital cellulitis is an infection of the orbital soft tissue that could possibly lead to serious complications if treatment is delayed. It is important to differentiate this condition from a less life-threatening condition like preseptal cellulitis as orbital cellulitis would require a more aggressive treatment than the former condition. The present case discusses about a patient who was diagnosed with orbital cellulitis and developed complications from the disease. The delayed administration of the appropriate antibiotic subsequently led to the patient’s death. The delay was because of the reason that the patient belonged to the immunocompromised group who harbour different causative organism than the normal population.